Education, experience and productivity of labor in Chinaes township and village enterprises : the case of Jiansu Province. - Liu, Yunhua. (2008)
In this paper, we analyze the productivity of different categories of labor and capital by estimating a production function using micro data of 140 industrial township and village enterprises located in 15 countries in Jiansu provience for the year 1989 and 1990.